Market of Plant Varieties in Ukraine: Green Pea (Pisum sativum L partim) - О. В. Свинарчук; О. І. Безручко (Plant Varieties Studying and Protection)
The article reflects economical value of a valuable food crop, field pea used chiefly as a vegetable (Pisum sativum L partim), its origin and distribution both in the worldwide scale and in our country, establishment of its varietal resources. Exhausting description is provided to new varieties of pea used chiefly as a vegetable, which have been listed in the State Register of Varieties Suitable for Dissemination in Ukraine in 20010-2011 for the harvest in 2012, and for which official description is available.